Experiences of women migrant workers and their reintegration status in Nepal - Khatiwada , Padma Prasad; Bohara, Pradeep (Educational Journal, 2024)
This paper explores the experiences of women migrant workers and their reintegration status in Nepal, with a specific focus on also includes the improving of new reintegration policies for returnee women. It employs a qualitative approach; information collected from two municipalities: Dakshinkali and Tarkeshwar of Kathmandu district. Through the Focus Group Discussion and In-Depth Interviews were conducted among 48 and 40 returnee women, the study captured their lived realities. A majority of participants belonged to Janajati/Indigenous nationalities (62.5% in FGDs; 70% in IDIs) and practiced Hinduism. Nearly two-fifths (35%) of FGD respondents and one-fifth (17%) of IDI respondents took the route through India to reach third countries, highlighting a high risk of trafficking. Over two-fifths of them were below 24 years of age. Documentation status revealed that 31percent of FGD respondents and 37.5 percent of IDI respondents were un-documented. While most returnees demonstrated a clear understanding of the concept’s “return” and “reintegration,” they reported inadequate support upon return especially during the lockdown period underscoring an urgent need for immediate reintegration planning to aid vulnerable returnees and facilitate family reunification. Participants emphasized the importance of social, economic, and psychosocial reintegration support.